HUBUNGAN HASIL BELAJAR MICROTEACHING DENGAN KEMAMPUAN MENGAJAR MAHASISWA PLP PRODI PENDIDIKAN TEKNOLOGI INFORMASI - Hasibuan, Risman Saputra; Wahyudi, Sri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: One of the strategic efforts in preparing professional teachers is through the implementation of learning programs that focus on teaching practice skills, such as microteaching and School Field Practice (PraktikLapanganPersekolahan or PLP). This study aims to determine the extent of the relationship between students' learning outcomes in the Microteaching course and their teaching ability during PLP at the Information Technology Education Study Program, Faculty of Education, Universitas Rokania. This research employs a quantitative approach with a correlational research design. Data were obtained through documentation of final grades in the Microteaching course and observations of students’ teaching performance during PLP. The results of the Pearson correlation analysis revealed an r value of 0.93, indicatinga very strong and positive relationship between the two variables. These findings suggest that students who achieve good results in Microteaching tend to demonstrate more optimal teaching abilities in the field. Therefore, this study emphasizes the critical role of Microteaching in preparing the pedagogical readiness and competence of future teachers. The findings also provide input for curriculum development to ensure that Microteaching learning becomes more applicable, contextual, and aligned with field needs. Keyword:Microteaching, TeachingAbility, PLP, Correlation, Information Technology  Education Abstrak:Salah satu upaya strategis dalam menyiapkan guru yang profesional adalah melalui penyelenggaraan program pembelajaran yang menitikberatkan pada keterampilan praktik mengajar, seperti microteaching dan Praktik Lapangan Persekolahan (PLP). Penelitian ini bertujuan untuk mengetahui sejauh mana hubungan antara capaian pembelajaran mahasiswa pada mata kuliah Microteaching dengan kemampuan mengajarnya pada saat PLP di Program Studi Pendidikan Teknologi Informasi, Fakultas Ilmu Pendidikan, Universitas Rokania. Penelitian ini menggunakan pendekatan kuantitatif dengan desain penelitian korelasional. Data diperoleh melalui dokumentasi nilai akhir mata kuliah Microteaching dan observasi kinerja mengajar mahasiswa pada saat PLP. Hasil analisis korelasi Pearson menunjukkan nilai r sebesar 0,93 yang menunjukkan hubungan yang sangat kuat dan positif antara kedua variabel tersebut. Temuan ini menunjukkan bahwa mahasiswa yang memperoleh hasil baik pada Microteaching cenderung menunjukkan kemampuan mengajar yang lebih optimal di lapangan. Oleh karena itu, penelitian ini menekankan pentingnya peran Microteaching dalam mempersiapkan kesiapan dan kompetensi pedagogik calon guru. Temuan ini juga memberikan masukan bagi pengembangan kurikulum agar pembelajaran Microteaching menjadi lebih aplikatif, kontekstual, dan selaras dengan kebutuhan lapangan. Kata kunci:Microteaching, Teaching Ability, PLP, Correlation, Information Technology  Education